Potential of filamentous fungi in the biodegradation of petroderivatives and evaluation of the effect of surfactants - Ferreira, Hozana de Souza; Caldas, Maria Catarina de Farias; Nascimento, Pollyana Pereira do; Barata, Maria Inez Campello; Takaki, Galba Maria de Campos; Andrade, Rosileide Fontenele da Silva (Seven Editora, 2023)
The contamination of the environment by petroleum products is a current and growing concern due to high toxicity and difficult removal. New ecologically viable technologies, such as bioremediation, have been gaining prominence for using microorganisms and their metabolites to remove or degrade pollutants that affect marine and terrestrial ecosystems. In this context, the objective of this work was to evaluate the growth potential of filamentous fungi (Aspergillus foetidus  and Rhizopus arrhizus) in petroderivatives, thus evaluating the potential of fungi  in the  biodegradation of petroderivatives (burnt motor oil, kerosene and diesel oil), in the presence and absence of surfactants. Therefore, the microorganisms were submitted to acclimatization in Sabouraud solid medium supplemented with different concentrations of burned motor oil (0%, 3% and 5%). Growth occurred during 72h at 28ºC. Then, the microorganisms were transferred to tubes containing Haas Bushnel medium and the 2,6-dichlorophenol-indophenol redox indicator (DCPIP) in the presence and absence of surfactants (natural and chemical). The results showed that Aspergillus foetidus and Rizopus arrhizus were able to grow at the maximum concentration of the petroderivative (5%), being therefore selected for the study of biodegradation. Aspergillus foetidus acclimatized with 5% of the burned engine oil was able to degrade (100%) the kerosene, both in the presence and absence of surfactants (chemical and natural). For the biodegradation of burnt engine oil (OQM) by Aspergillus foetidus the natural surfactant acted as a facilitating agent of biodegradation resulting in 100% degradation.  Rhizopus arrhizus showed excellent biodegradation potential of diesel oil (100%), both in the presence and absence of surfactants (chemical and natural). Therefore, Aspergillus foetidus  and Rhizopus arrhizus are promising microorganisms for biodegradation applications of kerosene and diesel oil, respectively. In addition, it was possible to prove that the surfactants (chemical and natural) did not show significant influence on the biodegradation of petroderivatives. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-005